143k views
2 votes
Solve for x.

6(x – 1) = 9(x + 2)

User Wdg
by
6.7k points

2 Answers

3 votes
Let's solve your equation step-by-step.
6(x−1)=9(x+2)

Step 1: Simplify both sides of the equation.
6(x−1)
=9(x+2)

Simplify:

(6)
(x)
+(6)(−1)
=(9)(x)+(9)(2)
(Distribute)
6x
+
−6
=9x+18

6x
−6
=9x+18

Step 2: Subtract 9x from both sides.
6x
−6
9x
=9x+189x

3x
−6
=18

Step 3: Add 6 to both sides.
3x
−6
+6
=18+6

3x
=24

Step 4: Divide both sides by -3.
3x
−3
=24−3

x=−8

Answer: x= -8

-Hope I helped.
User Alexander Pankin
by
6.4k points
6 votes

Answer: The required solution is x = -8.

Step-by-step explanation: We are given to solve the following equation for x :


6(x-1)=9(x+2)~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)

To solve the given equation for x, we must take all the terms involving x on one side and the other constant terms on the other side of the equation.

From equation (i), we get


6(x-1)=9(x+2)\\\\\Rightarrow 6x-6=9x+18\\\\\Rightarrow 9x-6x=-6-18\\\\\Rightarrow 3x=-24\\\\\Rightarrow x=-(24)/(3)\\\\\Rightarrow x=-8.

Thus, the required solution is x = -8.

User Zander Rootman
by
5.8k points